Impact of rotor-casing effusion cooling on turbine performance and operating point: an experimental, computational, and theoretical study - Adams, MG; Adami, P; Collins, M; Beard, PF; Chana, KS; Povey, T (American Society of Mechanical Engineers, 2021)
It is known that a secondary effect of rotor-casing effusion cooling is to modify and potentially spoil the rotor over-tip leakage flow. Studies have shown both positive and negative impacts on high-pressure (HP) stage aerodynamic performance and heat transfer, although there remains no consensus on whether the net effect is beneficial when both aerodynamic and thermal effects are accounted for simultaneously. An effect that has not been extensively discussed in the literature is the change in stage operating point that arises due to mass introduction midway through the machine. This effect complicates the analysis of the true performance impact on a turbine and must be accounted for in an assessment of the overall benefit of such a system. In this paper, we develop a low-order ("mean-line") analysis in an attempt to bring clarity to this issue. We then present results from experiments conducted in the Oxford Turbine Research Facility, a 1.5-stage transonic rotating facility capable of matching non-dimensional engine conditions. In the experiments, effusion cooling was implemented over a sector of the rotor casing spanning 24 degrees or four rotor-blade pitches. Rotor-exit radial traverse and HP vane loading measurements were conducted locally to the cooled sector. Results are compared to baseline tests conducted without cooling. To assess the degree to which experimental results with only a sector of the annulus cooled would provide an accurate indication of stage operating point changes (when measured local to the annulus) in an annular (engine-like) environment, unsteady Reynolds-averaged Navier-Stokes (URANS) simulations were performed. In particular, simulations of a full annulus with an effusion-cooled sector were compared to a periodic simulation with fully annular effusion cooling. The results-perhaps surprisingly-suggest that a cooled sector is sufficient to infer the changes in an annular system, provided measurements are performed locally to the sector. Experiments conducted with fixed 1.5-stage boundary conditions showed increases in both mid-stage static pressure and stage-exit total pressure with cooling. The mean-line model and URANS predictions were in good agreement with the experimental data and also showed an increase in stage reaction and a reduction in turbine-inlet (mainstream) mass flowrate with cooling. Finally, the URANS predictions were used to show that with cooling, there are changes both locally to the cooled casing (changes to the tip-leakage and secondary flow structures) and globally (changes to the bulk-flow velocity triangles). An absolute stage efficiency benefit of 0.7% was predicted for a coolant-to-mainstream mass flowrate ratio of 2.2%. By running with a number of different boundary conditions, steady RANS simulations were used to estimate the relative contributions to the efficiency improvement due to the changes in operating point and aerodynamics in the blade-tip region. For the present configuration, both changes contribute positively to the improvement in stage efficiency.